x²y"-(2x+1)y'+y²=0
Write the differential equation in standard form: "y''-\\frac{2x+1}{x^2}y'+\\frac{y^2}{x^2}=0"
We have "P(x)=-\\frac{2x+1}{x^2}" and "Q(x)=\\frac{1}{x^2}" , so "x= 0" is a singular point. Taking limits we get "lim_{x\u21920}xP(x) = 1" and "lim_{x\u21920}x^2Q(x) = 0" . Therefore "x= 0" is a regular singular point. We look for a solution of the form "y(x) =\u2211^\u221e_{n=0}a_nx^{n+r}" . Plug the series into the equation to get
"y(x) =\u2211^\u221e_{n=0}a_nx^{n+r}\\\\\n y' =\u2211^\u221e_{n=0}(n+r)a_nx^{n+r-1}\\\\\n y'' =\u2211^\u221e_{n=0}(n+r)(n+r-1)a_nx^{n+r-2}"
"y'' =x^2\u2211^\u221e_{n=0}(n+r)(n+r-1)a_nx^{n+r-2}-2x\u2211^\u221e_{n=0}(n+r)a_nx^{n+r-1}-\u2211^\u221e_{n=0}(n+r)a_nx^{n+r-1}+(\u2211^\u221e_{n=0}a_nx^{n+r})^2=0"
"\\implies y'' =\u2211^\u221e_{n=0}(n+r)(n+r-1)a_nx^{n+r}-\u2211^\u221e_{n=0}2(n+r)a_nx^{n+r}-\u2211^\u221e_{n=0}(n+r)a_nx^{n+r-1}+(\u2211^\u221e_{n=0}a_nx^{n+r})^2=0"
Upon re-arrangement we get
"(r(r-1)-2r)a_0x^r+\\sum_{n=0}^\\infin \\{[(n+r+1)(n+r+3)]q_{n+1}-(n+r-1)a_n\\}x^{n+r}"
Equating the powers of x yields
But "a_0 \\ne 0" implies that "r= 0,3" . Solving for the "a_n\u2019s" we get
For r=0
"a_{n+1}=\\frac{a_n}{n+3}\\\\\na_1=\\frac{a_0}{3}\\\\\na_2=\\frac{a_1}{4}=\\frac{a_0}{4 \\cdot 3}=\\frac{a_0 \\cdot 2 \\cdot 1}{4 \\cdot 3 \\cdot 2 \\cdot 1}=\\frac{2!}{4!}a_0 \\\\ \na_3=\\frac{a_2}{5}=\\frac{a_0}{5 \\cdot 4 \\cdot 3}=\\frac{a_0 \\cdot 2 \\cdot 1}{5 \\cdot4 \\cdot 3 \\cdot 2 \\cdot 1}=\\frac{2!}{5!}a_0 \\\\\n.\\\\\n.\\\\\n.\\\\\na_n=\\frac{2!}{(n+3)!}a_0"
For r=3
"a_{n+1}=\\frac{a_n}{n+6}\\\\\na_1=\\frac{a_0}{6}\\\\\na_2=\\frac{a_1}{7}=\\frac{a_0}{7 \\cdot 6}=\\frac{a_0}{7 \\cdot 6!}\\\\ \na_3=\\frac{a_2}{8}=\\frac{a_0}{8 \\cdot 7 \\cdot 6}=\\frac{a_0}{8 \\cdot7 \\cdot 6!} \\\\\n.\\\\\n.\\\\\n.\\\\\na_n=\\frac{a_0}{(n+6)!}"
Two linearly independent Frobenius series (with "a_0= 1" ) are given by
Comments
Leave a comment